2018
DOI: 10.1523/jneurosci.0378-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Hippocampal Inputs Preferentially Drive Corticocortical Neurons in the Infralimbic Prefrontal Cortex

Abstract: Inputs from the ventral hippocampus (vHPC) to the prefrontal cortex (PFC) play a key role in working memory and emotional control. However, little is known about how excitatory inputs from the vHPC engage different populations of neurons in the PFC. Here we use optogenetics and whole-cell recordings to study the cell-type specificity of synaptic connections in acute slices from the mouse PFC. We first show that vHPC inputs target pyramidal neurons whose cell bodies are located in layer (L)2/3 and L5 of infrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

17
100
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 56 publications
(50 reference statements)
17
100
2
Order By: Relevance
“…To isolate monosynaptic connections, we 274 included TTX (1 μM), 4-AP (10 μM), and elevated Ca 2+ (4 mM), which blocks action potentials 275 (APs) but restores presynaptic release (Little and Carter, 2012;Petreanu et al, 2009). We also 276 kept the light intensity and duration constant within pairs, allowing us to account for differences in 277 viral expression across animals and slices (Liu and Carter, 2018). We found that vHPC inputs 278 evoked robust EPSCs at CCK+ interneurons, which were similar in amplitude to IT cells ( Fig.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…To isolate monosynaptic connections, we 274 included TTX (1 μM), 4-AP (10 μM), and elevated Ca 2+ (4 mM), which blocks action potentials 275 (APs) but restores presynaptic release (Little and Carter, 2012;Petreanu et al, 2009). We also 276 kept the light intensity and duration constant within pairs, allowing us to account for differences in 277 viral expression across animals and slices (Liu and Carter, 2018). We found that vHPC inputs 278 evoked robust EPSCs at CCK+ interneurons, which were similar in amplitude to IT cells ( Fig.…”
mentioning
confidence: 95%
“…The vHPC primarily projects to the ventral medial PFC in rodents, with axons most prominent in 55 layer 5 (L5) of infralimbic (IL) PFC (Phillips et al, 2019). These excitatory inputs contact multiple 56 populations of pyramidal cells, and are much stronger at intratelencephalic (IT) cells than nearby 57 pyramidal tract (PT) cells (Liu and Carter, 2018). vHPC inputs can drive robust firing of IT cells 58 (Liu and Carter, 2018), which may be important for maintaining activity during behavioral tasks 59 (Padilla-Coreano et al, 2016; Spellman et al, 2015).…”
mentioning
confidence: 99%
See 3 more Smart Citations